Weight Loss Due to a Very Low Calorie Diet Differentially Affects Insulin Sensitivity and Interleukin-6 Serum Levels in Nondiabetic Obese Human Subjects - Oberhauser, F.; Schulte, D. M.; Faust, M.; Güdelhöfer, H.; Hahn, M.; Müller, N.; Neumann, K.; Krone, W.; Laudes, M. (Hormone and Metabolic Research, 2012)
Inflammatory mechanisms are involved in the pathogenesis of type 2 diabetes with interleukin (IL)-6 being particularly important. While long term exercise has been shown to be associated with reduction in IL-6 serum levels in several reports, the discussion on the effect of dietary intervention on IL-6 serum levels is controversial. In the present study, we aimed to investigate the effect of weight loss due to a very low calorie diet (VLCD) on insulin sensitivity and IL-6 serum levels in nondiabetic obese human individuals. 10 patients with obesity were examined during 12 weeks of a VLCD (800 kcal/d). Body composition was measured by impedance analysis. Blood samples were taken before, during, and after the dietary intervention. Leptin, adiponectin, and IL-6 serum levels were measured by ELISA. The body weight decreased significantly from 123.9±6.2–103.5±5.6 kg with a significant reduction in body fat content (43.2±2.3–36.1±3.1%). Leptin levels exhibited a significant decrease from 56.8±5.6–27.9±5.6 ng/ml while adiponectin levels increased significantly from 7.5±0.9–10.6±1.1 μg/ml. Thereby the leptin-to-adiponectin ratio, a novel marker for insulin sensitivity, significantly improved. Mean IL-6 serum concentrations were within the normal range (3.2±0.8 pg/ml) before the study and were not significantly altered by the nutritional therapy. Despite improvement of insulin sensitivity, IL-6 serum levels did not change throughout the study period, suggesting that in nondiabetic obese human subjects IL-6 might have only a minor role in the impairment of insulin sensitivity.
Keywords: inflammation; metabolism; obesity